Pendidikan Hati Bagi Anak - Rizni Ramadhani; Lady Shania Wulandari; Hawa Ihsani (STIKes Ibnu Sina Ajibarang, 2024)
This study examines the concept of heart education for children, focusing on character and emotional development. The main issue addressed is the lack of educational approaches that deeply shape children’s character, with the aim of formulating effective methods for heart education. A qualitative approach, including literature analysis and expert interviews, was used. Results indicate that heart education enhances empathy, emotional control, and morals in children. It concludes that heart education is crucial for personality formation, with a recommendation for its integration in schools and families